Self-Presentation of Student Athletes at the University Muhammadiyah Surakarta through Social Media Twitter - Rahman, Revina Alifia; Nofandrilla, Nieldya (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: To find out how student-athletes at the Muhammadiyah University of Surakarta do a self-presentation through social media platform Twitter. Methodology: The type of research used is descriptive qualitative using a self-presentation strategy by Jones and Pittman (1982), namely: ingratiation, self-promotion, intimidation, exemplification, and supplication. The data is collected through interviews and observation of accounts and Twitter report. Results : The results showed that athletes in making self-presentations only used several self-presentation strategies, namely ingratiation, self-promotion, and exemplification. Applications/Originality/Value: The difference with the previous research is that the object used in this study used athletes as objects while the latest research used politicians.